2013
DOI: 10.1111/pedi.12060
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of physical activity and sedentary behavior intervention studies in youth with type 1 diabetes: study characteristics, intervention design, and efficacy

Abstract: Few RCTs explored the efficacy of unsupervised theory-based physical activity and/or sedentary behavior interventions in youth with type 1 diabetes. Limited reporting made comparison of findings challenging. There was an overall significant beneficial effect of physical activity on HbA1c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
104
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 34 publications
8
104
1
8
Order By: Relevance
“…Similar result was found in previous study [20], in which severe hypoglycemia was independent risk and not related to frequency of exercise.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar result was found in previous study [20], in which severe hypoglycemia was independent risk and not related to frequency of exercise.…”
Section: Discussionsupporting
confidence: 80%
“…Studies of training program on group of adolescents with T1DM revealed that regular physical exercise significantly decrease HbA1c [8,18]. Other studies revealed similar significant results [4][5][6]9,19,20] which showed that improvement was associated with the frequency of physical activity [4,20]. Slight decrease in HbA1c was observed with combination of aerobic and muscle strength exercise training program [10,14] and was better with competitive sport [21].…”
Section: Discussionsupporting
confidence: 58%
“…It is also the first study to incorporate a physical activity protocol with high-intensity sprints which resembles everyday activities of young people. The scenario of not announcing physical activity to the system and not providing uncovered snacks relates to real-life situations experienced by an adolescent population often unable to adhere to the recommended measures before physical activity [2,8].…”
Section: Discussionmentioning
confidence: 99%
“…Regular physical activity is a fundamental part of type 1 diabetes management recommendations [1] and has a positive impact on cardiovascular health, insulin requirement, body fitness and general wellbeing [2]. Recent data from large diabetes registries have shown a positive correlation between physical activity and metabolic control [3].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding activity and exercise within the school environment, most of the participants answered that diabetic children could attend the physical activity sessions. However, they were not aware about the measures that should be taken before, during or after any activity -such as blood glucose monitoring before and after any activity, consuming additional carbohydrates, and if using an insulin pump, decisions related to whether the pump should be disconnected or temporary basal rates set [25].…”
Section: Discussionmentioning
confidence: 99%